Amyloid beta peptide ratio 42/40 but not A beta 42 correlates with phospho-Tau in patients with low- and high-CSF A beta 40 load - Wiltfang, Jens; Esselmann, Hermann; Bibl, Mirko; Hüll, Michael; Hampel, Harald; Kessler, Holger; Frölich, Lutz; Schröder, Johannes; Peters, Oliver; Jessen, Frank; Luckhaus, Christian; Perneczky, Robert; et al. (Journal of neurochemistry, 2007)
Neurochemical dementia diagnostics (NDD) can significantly improve the clinically based categorization of patients with early dementia disorders, and the cerebrospinal fluid (CSF) concentrations of amyloid beta peptides ending at the amino acid position of 42 (A beta x-42 and A beta 1-42) are widely accepted biomarkers of Alzheimer's disease (AD). However, in subjects with constitutively high- or low-CSF concentrations of total A beta peptides (tA beta), the NDD interpretation might lead to erroneous conclusions as these biomarkers seem to correlate better with the total A beta load than with the pathological status of a given patient in such cases. In this multicenter study, we found significantly increased CSF concentrations of phosphorylated Tau (pTau181) and total Tau in the group of subjects with high CSF A beta x-40 concentrations and decreased A beta x-42/x-40 concentration ratio compared with the group of subjects with low CSF A beta x-40 and normal A beta ratio (p<0.001 in both cases). Furthermore, we observed significantly decreased A beta ratio (p<0.01) in the group of subjects with APOE epsilon 4 allele compared with the group of subjects without this allele. Surprisingly, patients with low-A beta x-40 and the decreased A beta ratio characterized with decreased pTau181 (p<0.05), and unaltered total Tau compared with the subjects with high A beta x-40 and the A beta ratio in the normal range. We conclude that the amyloid beta concentration ratio should replace the 'raw' concentrations of corresponding A beta peptides to improve reliability of the neurochemical dementia diagnosis.